Social Entrepreneurship: a poorly recognised element of Entrepreneurship Education at HE institutions - Reichel, Janusz; Rudnicka, Agata; Socha, Błażej (Przedsiębiorczość - Edukacja, 2022)
Entrepreneurship has become a critical competency in the 21st century. Higher education (HE) institutions, aware of the need to answer market needs, have started several initiatives to develop entrepreneurial education. However, the concept of social entrepreneurship does not seem to be widely known among graduates. The aim of the article is an attempt to assess entrepreneurial competencies and knowledge in the field of social entrepreneurship. The authors have focused on the teaching of social entrepreneurship, an undervalued element of entrepreneurial education in HE institutions. For that purpose, a case study of a course introduced at the academic level was used, which allowed answering the following questions: Is social entrepreneurship known among students as a possibility for entrepreneurial development? How do they assess a course in social entrepreneurship regarding its usefulness and ability to develop competencies? The study shows that social entrepreneurship seems to be a form that is not well recognised, which means that students do not even have the chance to know the whole entrepreneurship picture. Researwch has shown students’ positive approach to a course devoted to social entrepreneurship and its potential to develop the knowledge and skills to run one’s venture in the future. The results are a part of a broader trend related to the need for social entrepreneurship in HE institutions.